Review of the type material of three species of Polietina Schnabl & Dziedzicki (Diptera, Muscidae) - Nihei,Silvio Shigueo (2004)
The type material of three species of Polietina Schnabl & Dziedzicki, 1911 was examined. Polietina flavidicincta (Stein, 1904) is redescribed and a lectotype is designated; P. stellata (Couri, 1982) is considered junior synonym of P. flavithorax (Stein, 1904), and for the latter a lectotype is designated. The neotype previously designated is considered invalid.